Synthesis of a BiFeO3 nanowire-reduced graphene oxide based magnetically separable nanocatalyst and its versatile catalytic activity towards multiple organic reactions. Issue 100 (13th October 2016) - Moitra, Debabrata; Ghosh, Barun Kumar; Chandel, Madhurya; Ghosh, Narendra Nath
Abstract : Herein, we report for the first time synthesis of a BiFeO3 nanowire-reduced graphene oxide nanocatalyst (BFO–RGO) using a hydrothermal method. Abstract : Herein, we report for the first time synthesis of a BiFeO3 nanowire-reduced graphene oxide nanocatalyst (BFO–RGO) using a hydrothermal method. The BFO–RGO nanocatalyst exhibited excellent catalytic activity towards Biginelli reaction, Click reaction, styrene epoxidation, 4-NP reduction and a herbicide, (trifluralin) reduction. The novelty of this catalyst lies in its high catalytic efficiency towards many organic reactions, easy separation and good reusability.